Direct discrete time design of robust state derivative feedback control laws - Rossi, Fernanda Quelho; Galvão, Roberto Kawakami Harrop; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Assunção, Edvaldo [UNESP] (Taylor & Francis, 2018)
This paper is concerned with the problem of designing robust state derivative feedback control laws in discrete time. The main contribution consists of a method for recasting a continuous time state space model in the form of a discrete time model formulated in terms of the state derivative. Uncertain input delays and parametric uncertainties in polytopic form can be propagated from the original state space representation to the resulting state derivative model. Therefore, robust control techniques originally developed for discrete time state space models can be directly employed to design the state derivative feedback law. Three computational examples are presented for illustration. The first example highlights the importance of accounting for the effect of sampling in the design procedure. More specifically, a linear quadratic regulation problem involving the state derivative is addressed. The second example involves the design of a robust predictive controller in the presence of input constraints and uncertain time delay. Finally, the third example is concerned with robust pole placement in the presence of parametric uncertainty.
Keywords: direct discrete time design; robust control; robust pole placement; robust predictive control; State derivative feedback